Examining the Positivity Effect in Autobiographical Memory Across Adulthood. (March 2015) - Siedlecki, Karen L.; Hicks, Stephanie; Kornhauser, Zachary G. C.
The positivity effect in memory is characterized by enhanced memory for emotionally positive information or decreased memory for emotionally negative information with increased age. The goals of the current study were to (a) examine the positivity effect in autobiographical memory using instructions that limited experimental constraints, (b) examine the relationship between memory valence and subjective well-being, and (c) examine the relationship between age and other memory characteristics across adulthood. In the current study, 281 individuals between the ages of 18 and 94 ( M age  = 53.14, SD  = 17.04) completed a modified Memory Experiences Questionnaire using online survey methods. Participants answered questions about emotional valence and other phenomenological characteristics regarding two memories, including any specific memory of their choosing and a personally meaningful memory. Results indicated that memory valence was unrelated to age, thus failing to provide evidence for the positivity effect. However, memory valence was found to be a significant predictor of life satisfaction. Age moderated the relationship between memory valence and subjective well-being but did so differently across the two memories. Age was also associated with increased vividness, coherence, sensory detail, time clarity, and a first-person perspective for the personally meaningful memory.